1992
DOI: 10.1164/ajrccm/146.4.965
|View full text |Cite
|
Sign up to set email alerts
|

Lung Mechanics and Gas Exchange during Pressure-Control Ventilation in Dogs: Augmentation of CO2Elimination by an Intratracheal Catheter

Abstract: Increased awareness of pressure-related injury to the alveolar-capillary interface has renewed interest in modes of ventilation that limit alveolar distention such as pressure-controlled ventilation (PCV). We examined respiratory system mechanics and gas exchange during PCV in six dogs. Our data conformed to the predictions of our single-compartment mathematical model of respiratory dynamics during PCV (J Appl Physiol 1989; 67:1081-92). For a fixed pressure (Pset) and inspiratory time fraction (Tl/Ttot) (15 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(40 citation statements)
references
References 11 publications
0
39
0
1
Order By: Relevance
“…The technique of tracheal gas insufflation was described as long ago as 1969 [28], and has P a co 2 reduction with tracheal gas insufflation as an adjunct to pressure or volume controlled ventilation [8,9,11,12,15,16,29]. Expiratory washout is potentially attractive as it does not augment inspiratory tidal volume and may cause less dynamic hyperinflation than continuous tracheal gas insufflation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique of tracheal gas insufflation was described as long ago as 1969 [28], and has P a co 2 reduction with tracheal gas insufflation as an adjunct to pressure or volume controlled ventilation [8,9,11,12,15,16,29]. Expiratory washout is potentially attractive as it does not augment inspiratory tidal volume and may cause less dynamic hyperinflation than continuous tracheal gas insufflation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all such volumes were corrected for the compliance of the breathing circuit. This was done using the formula 2:3 Â peak airway pressure 2 PEEP ; where 2.3 is the compliance of the breathing system, expressed as ml.cmH 2 O 21 [11]. This breathing system compliance was obtained from a previously constructed pressure/volume curve for the breathing system.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Nahum et al developed an animal model combining conventional mechanical ventilation with tracheal gas insufflation via a catheter positioned above the carina and inserted in parallel with the ETT. These authors showed that the technique decreased PaCO 2 (Nahum et al 1992a). Efficacy depended on the flow rate used (up to 10 L/min) and was little dependent on catheter positioning.…”
Section: Safety Considerationsmentioning
confidence: 97%
“…Minimal changes in residual volume cause huge changes in PaCO 2 . This implies in the use of TGI when the VD/VT ratio is elevated (permissive hypercapnia) 6,10 . During the use of TGI, one should ideally monitor PEEP, peak inspiratory pressure, airway resistance, pulmonary complacency, and tidal volume to prevent possible complications 11 .…”
Section: Introductionmentioning
confidence: 99%